STRATEGI PEMASARAN JASA PENDIDIKAN DI MTS MINAT KESUGIHAN - Nuha, Muhammad Ulin (Jurnal Tawadhu, 2022)
Marketing strategy is an important thing to do for an educational institution. Marketing activities are useful for introducing educational services offered to education customers, which in this case are prospective students and the general public. The purpose of this study was to identify and describe the marketing strategy of educational services in the form of segmentation, targeting, positioning at MTs MINAT Kesugihan. In addition to using this method, marketing activities also use the marketing mix as a marketing tool. The method in this research is a qualitative method. Researchers collect data by observation, interviews and document studies. The data analysis techniques that researchers use are data reduction, data presentation and conclusion drawing. The results showed that the marketing strategy for educational services at MTs MINAT Kesugihan was quite optimal. This can be seen from the segmentation strategy implemented by using several approaches, the target market is only among students in Kesugihan and students under the auspices of Ya Bakii, Madrasah positioning with superior programs, character habituation, and extracurriculars are advantages. In the continuity of marketing activities, it turns out that MTs MINAT has a fairly long process starting from the pre-marketing phase to the marketing activity phase. The sustainability of marketing activities is also influenced by the good name of Islamic boarding schools and alumni who are active and active in the community so that they indirectly have a positive impact on the existence of madrasas in the eyes of the community.